A Multiple Correspondence Analysis of Patterns of CBD Use in Hemp and Marijuana Users - Vilches, Joseph R.; Taylor, Mackenzie B.; Filbey, Francesca M. (Frontiers in Psychiatry, 2021)
Background: With the passing of the 2018 Agriculture Improvement Act that legalized hemp-derived products, i.e., cannabidiol (CBD), the use of CBD has increased exponentially. To date, the few studies that have characterized individuals who use CBD suggest that co-use of CBD and tetrahydrocannabinol (THC)-dominant cannabis, i.e., marijuana, is highly prevalent. It is, therefore, important to investigate the relationship between CBD use and marijuana use to understand the antecedents and consequences of co-use of these two cannabis products. Methods: We conducted an online survey using structured questionnaires to determine differences in CBD users with (CBD+MJ) and without co-morbid marijuana use. Group comparisons were carried out using chi-square tests and ANOVA. Multiple correspondence analysis (MCA) with bootstrap ratio testing was performed to examine the relationship between the categorical data. Results: We received 182 survey responses from current CBD users. CBD+MJ had more types of CBD administration (F= 17.07, p < .001) and longer lifetime duration of CBD use (χ2 = 12.85, p < .05). Results from the MCA yielded two statistically significant dimensions that accounted for 77% of the total variance. Dimension 1 associated CBD+MJ with indication of CBD use for medical ailments, use of CBD for more than once a day for longer than two years, applying CBD topically or consuming it via vaping or edibles, being female, and, having lower educational attainment. Dimension 2 separated the groups primarily on smoking-related behaviors where CBD+MJ was associated with smoking CBD and nicotine. Conclusions: Identifying the factors that influence use of CBD and marijuana can inform future studies on the risks and benefits associated with each substance as well as the impacts of policies related to cannabis-based products.